THE FUNCTIONS OF SWEAR WORDS IN THE “CELEBRITY MEAN TWEETS” IN JIMMY KIMMEL LATE SHOW - Nurul Fitri (Universitas Batanghari Jambi, 2018)
This research is aimed at describing the functions of Swear Words in the “Celebrity Mean Tweets” in Jimmy Kimmel Late Show. The data is taken from the tweets of the celebrities in Jimmy Kimmel Late Show. The design of this research is qualitative research. In collecting the data, the researcher retypes all the swear words that are found in the celebrity read mean tweets with left the tweet without swear words, change the data from video into the word file. Then, the technique for analyzing the data is by pointing out the functions of swear words used by those celebrities. The conclusion shows that there are four functions of swearing according to this data, there are the abusive swearing, the largest and the most frequent, the emphatic, the dysphematic and the lowest and least frequent, the idiomatic. Even though their functions are different, but they are connected in the relation; which they are used to either insult, emphasis, explain the vulgar situation and change the word, they still used to fill the swear words by its function, either insult people, emphasizing bad words, explain the vulgar situation to insult and change the word into insult word. Keywords: Swear Words, Social Media